FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN CASH DIVIDEND PADA BADAN USAHA MILIK NEGARA (BUMN) YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Prasetya, Hendra; Ariska, Ricky Angga (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2017)
This research is conducted to know the effect of debt to equity ratio, return on investment, and firm size on the dividend payout ratio at Badan Usaha Milik Negara (BUMN). Data in this research use secondary data and sampling technique in this research using purposive sampling technique. Sample criteria are BUMN that listing in BEI in 2012-2014, having profit during 2012-2014, and having complete financial report during 2012-2014. There are five companies that meet these criteria. Analyzer used in penenlitian is doubled linear regression. The results showed that debt to equity ratio, return on investment, and firm size have simultaneously effect to dividend payout ratio. Beside that, the results showed that only return on investment has partially effect on the dividend payout ratio. Debt on equity ratio and firm size have no partially effect on dividend payout ratio.